Web Services Messaging with JAX-RPC from chapter 5.
The last chapter introduced simple SOAP messaging. In this chapter, we move to the next level of sophistication and introduce a true messaging framework that forms the backbone of the EAI infrastructure developed in this book. This messaging framework enables Java applications to send and receive Java objects to and from web services using SOAP as the transport. It also enables asynchronous messaging whereby the sender of a message does not have to block waiting for the receiver to process it. We call our framework the Web Services Messaging Framework (WSMF). It is implemented using J2EE and Web Services standards and serves as the core messaging service used by all the non-JMS EAI applications developed in the remainder of this book.